Pripomočki in naprave za komunikacijo - Marot, Valerija (Rehabilitacija (Ljubljana), 2019)
Communication is an act of transferring information between two or more people. When individuals are not able to satisfy their communication needs through speech, special support and special techniques for overcoming the communication barriers are needed. Alternative and augmentative communication (AAC) techniques and devices contribute to more effective communication. Different systems of AAC include different techniques and devices. Low-tech AAC systems do not require electricity and electronics. High-tech AAC systems include various computer or non-computer electronic communication devices. In addition to the basic unit for communication, they can have additional electronic units that enable independent communication for people with physical disabilities.
Keywords: augmentative and alternative communication; CCN; Communication Aids for Disabled; communication devices; Communication Disorders; complex communication needs; KKP; kompleksne komunikacijske potrebe; komunikacijske naprave; komunikacijski pripomočki za osebe s posebnimi potrebami; motnje govora; nadomestna in dopolnilna komunikacija; rehabilitation